Comparative transcriptomics of sympatric species of coral reef fishes (genus: Haemulon) - Moisés A. Bernal; Groves B. Dixon; Mikhail V. Matz; Luiz A. Rocha (PeerJ, 2019)
Background Coral reefs are major hotspots of diversity for marine fishes, yet there is still ongoing debate on the mechanisms that promote divergence in these rich ecosystems. Our understanding of how diversity originates in this environment could be enhanced by investigating the evolutionary dynamics of closely related fishes with overlapping ranges. Here, we focus on grunts of the genus Haemulon, a group of coral reef fishes with 15 species in the Western Atlantic, 11 of which are syntopic. Methods Wild fish samples from three sympatric species of the Caribbean: Haemulon flavolineatum, H. carbonarium and H. macrostomum, were collected while SCUBA diving. RNA was extracted from livers, and the transcriptomes were assembled and annotated to investigate positive selection (Pairwise dN/dS) and patterns of gene expression between the three species. Results Pairwise dN/dS analyses showed evidence of positive selection for genes associated with immune response, cranial morphology and formation of the anterior–posterior axis. Analyses of gene expression revealed that despite their sympatric distribution, H. macrostomum showed upregulation of oxidation-reduction machinery, while there was evidence for activation of immune response in H. carbonarium. Discussion Overall, our analyses suggest closely related grunts show important differences in genes associated with body shape and feeding morphology, a result in-line with previous morphological studies in the group. Further, despite their overlapping distribution they interact with their environment in distinct fashions. This is the largest compendium of genomic information for grunts thus far, representing a valuable resource for future studies in this unique group of coral reef fishes.